Ab initio local-energy and local-stress analysis of tensile behaviours of tilt grain boundaries in Al and Cu. (7th December 2016) - Wang, Hao; Kohyama, Masanori; Tanaka, Shingo; Shiihara, Yoshinori
Abstract: Tensile deformation and failure of Σ9 tilt grain boundaries (GBs) in Al and Cu have been examined by first-principles tensile tests (FPTTs). Local-energy and local-stress schemes were applied to clarify the variations of local energies and local hydrostatic stresses for all atoms during the deformation process. The GBs in Al and Cu exhibited quite different tensile behaviours in the FPTTs, despite their similar initial configurations. For the Al GB, there are two stages of deformation before failure. In the first stage, the back bonds of the interfacial bonds are mainly stretched, due to special high strength of the interfacial reconstructed bonds. In the second stage, the interfacial bonds begin to be significantly stretched due to high concentrated stresses, while stretching of the back bonds is suppressed. The atoms at the interfacial, back and bulk bonds have very different variations of local energies and local stresses during each stage, because the behaviour of each atom is significantly dependent on each local structural change due to the high sensitivity of sp electrons to the local environment in Al. The Cu GB has much higher tensile strength, and a natural introduction of stacking faults (SFs) occurs via the {111} 〈 112 〉 shear slip in the bulk regions between the interfaces before the maximum stress is reached. This is caused by the smaller SF energy and lower ideal shear strength of Cu than Al, and is triggered by highly accumulated local energies and stress at the interface atoms. The local-energy distribution around the SF is consistent with the previous theoretical estimation. After the introduction of the SF, the local energies and stresses of all the atoms in the Cu GB supercell tend to become similar to each other during the tensile process, in contrast to the inhomogeneity in the Al GB. The origins of the different tensile behaviours observed for Al and Cu GBs are discussed with respect to the different bonding natures of Al and Cu, which are dominated by three sp valence electrons per atom for Al and by fully occupied d bands and s electrons for Cu.